Analisis Ketahanan Penetrasi Subsoil Di Agroekosistem Kebun Kopi Robusta Di Kecamatan Karangploso, Kabupaten Malang - Ifadah, Nisfi Fariatul; Riyanto, Saniya Reizta; Jasmita, Adellia; Soemarno, Soemarno (Fakultas Pertanian Universitas Brawijaya, 2025)
Subsoil compaction indicator can be seen from the value of soil penetration resistance (SPR). Information related to the distribution of soil penetration resistance is important as the efforts to increase coffee production due to the relation to development of coffee roots, while at the research location does not have yet this information. Therefore, further research is needed to know the soil penetration resistance at several coffee ages with different soil depths and to analyze the relation between soil penetration resistance with other soil physical properties, coffee growth, as well as productivity of coffee crops in the Robusta coffee plantation. This research activity was carried out by survey method and purposive sampling method. The survey activities include making minipits, measuring soil penetration resistance at coffee plantation with a coffee plant age of 5 to >20 years at a soil depth of 0-20 cm, 20-40 cm, and 40-60 cm by using a hand penetrometer, taking soil samples, and measuring coffee plant growth. The results showed that soil penetration resistance (SPR) in smallholber coffee plantations in the coffee root zone is classified into the â€œMediumâ€ and â€œHighâ€ soil penetration resistance classes (1.34 MPa to 3.35 MPa). Variations in SPR values are caused by differences of cpffee age, agricultural activities in coffee plantations, and soil physical characteristics. Several physical properties of the soil that are closely related to the soil penetration resistance value are aggregate stability, water content, bulk density, porosity, silt content, and clay content. The soil penetration resistance value is closely related to the productivity of Robusta coffee, with a correlation coefficient value of -0.5936**.